Electrochemical Lignin Conversion. Issue 17 (11th August 2020) - Du, Xu; Zhang, Haichuan; Sullivan, Kevin P.; Gogoi, Parikshit; Deng, Yulin
Abstract: Lignin is the largest source of renewable aromatic compounds, making the recovery of aromatic compounds from this material a significant scientific goal. Recently, many studies have reported on lignin depolymerization and upgrading strategies. Electrochemical approaches are considered to be low cost, reagent free, and environmentally friendly, and can be carried out under mild reaction conditions. In this Review, different electrochemical lignin conversion strategies, including electrooxidation, electroreduction, hybrid electro‐oxidation and reduction, and combinations of electrochemical and other processes (e. g., biological, solar) for lignin depolymerization and upgrading are discussed in detail. In addition to lignin conversion, electrochemical lignin fractionation from biomass and black liquor is also briefly discussed. Finally, the outlook and challenges for electrochemical lignin conversion are presented. Abstract : Better lignin through electrochemistry : This comprehensive Review concerns electrochemical lignin conversion strategies, including electrooxidation, electroreduction, hybrid electro‐oxidation and reduction, and combination of electrochemical and other processes (e. g. biological, solar) for lignin conversion and upgrading. Electrochemical biomass fractionation for lignin separation is also briefly introduced.